Preventing Hospitalization in Mild Acute Pancreatitis Using a Clinical Pathway in the Emergency Department. Issue 8 (September 2018) - Kothari, Darshan; Babineau, Matthew; Hall, Matthew; Freedman, Steven D.; Shapiro, Nathan I.; Sheth, Sunil G.
Abstract : Goals: We created an observation pathway with close outpatient follow-up for patients with mild acute pancreatitis (AP) to determine its effect on admission rates, length of stay (LOS), and costs. Background: AP is a common reason for hospitalization costing 2.6 billion annually. Majority have mild disease and improve quickly but have unnecessarily long hospital stays. Study: We performed a pilot prospective cohort study in patients with AP at a tertiary-care center. In total, 90 patients with AP were divided into 2 groups: observation cohort and admitted cohort. Exclusion criteria from observation included end-organ damage, pancreatic complications, and/or severe cardiac, liver, and renal disease. Patients in observation received protocolized hydration and periodic reassessment in the emergency department and were discharged with outpatient follow-up. Using similar exclusion criteria, we compared outcomes with a preintervention cohort composed of 184 patients admitted for mild AP in 2015. Our primary outcome was admission rate, and secondary outcomes were LOS, patient charges, and 30-day readmission. Results: Admitted and preintervention cohorts had longer LOS compared with the observation cohort (89.7 vs. 22.6 h, P <0.01 and 72.0 vs. 22.6 h, P <0.01). The observation cohort admission rate was 22.2% lower than the preintervention cohort ( P <0.01) and had 43% lower patient charges (5281 vs. 9279, P <0.01). Moreover there were significantly fewer imaging studies performed (25 vs. 49 images, P =0.03) in the observation cohort. There were no differences in readmission rates and mortality. Conclusions: In this feasibility study, we demonstrate that a robust pathway can prevent hospitalization in those with AP and may reduce resource utilization without a detrimental impact on safety.